LACTIC ACID BACTERIA PROBIOTIC OF FISH’S GASTROINTESTINAL TRACT AS WEIGHT AND CHOLESTEROL BOOSTER IN BROILER MEAT - Astuti Astuti (Jurnal Penelitian Saintek, 2015)
This research was aimed at ﬁ nding the inﬂ uence of giving isolate probiotic Lactic Acid Bacteria (BAL) Streptococcus thermophillus from the ﬁ sh’s gastro-intestinal tract toward the broilers’ appearance including the enhancement of the weight, and the broilers’ cholesterol level. The subjects of the research are 40 roosters of broiler chicken, PT Multi Breeder Adirama at the age of 1 week. The probiotic of isolate treatment of BAL used in this research is Streptococcus thermophillus bacteria in the form of freeze dying from Nutrition Biochemical Laboratory, Veterinary Faculty of UGM. Treatment I was as the control (without BAL); the number of BAL in treatment II is 10 6  CFU/ml; the number of BAL in treatment III is 10  CFU/ml; and the number of BAL in treatment IV is 10  CFU/ml. The data recording for the performance was done every week including the weight enhancement. The data collection for cholesterol level enhancement was done at the end of the research. The data which were collected: the weight enhancement, and the broilers’ cholesterol level. The ﬁ nding shows that the treatment of giving lactic acid bacteria of Streptococcus thermophillus caused the broilers’ cholesterol decreased signiﬁ cantly; giving probiotic BAL is not inﬂ uenced toward the performance of growth while the best level of BAL is 108 CFU/ml. 8